2016
DOI: 10.1111/hir.12143
|View full text |Cite
|
Sign up to set email alerts
|

Where people look for online health information

Abstract: There is a need for continued efforts by librarians and health care professionals to train seekers of online health information to select websites using established guidelines and quality criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…LaValley et al [102] reported that almost 3/4 of Americans use commercially sponsored websites to satisfy their health information requirements, but stressed how different website types have different reasons for sponsoring health information, which may affect the website’s content and design. Hu and Sundar [103] showed that websites are preferred to bulletin boards, home pages, and blogs, and credibility was strongly associated with users’ perceptions of the relevance of the message associated to a certain source.…”
Section: Discussionmentioning
confidence: 99%
“…LaValley et al [102] reported that almost 3/4 of Americans use commercially sponsored websites to satisfy their health information requirements, but stressed how different website types have different reasons for sponsoring health information, which may affect the website’s content and design. Hu and Sundar [103] showed that websites are preferred to bulletin boards, home pages, and blogs, and credibility was strongly associated with users’ perceptions of the relevance of the message associated to a certain source.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that health information available on the Internet is sometimes scientifically incomplete or inadequate [16,17]. When the health information obtained from the Internet is of questionable quality, it may negatively influence the doctor-patient relationship [18,19]. The wide variability of resources on the Internet and the commercial interest of some providers can cause confusion to the user and make it difficult to locate accurate and reliable health information [17].…”
Section: Introductionmentioning
confidence: 99%
“…Dissemination of evidence, means of access and the effectiveness of that access are all explored in this quarter's issue of the Health Information and Libraries Journal.…”
Section: In This Issue…mentioning
confidence: 99%
“…'s mixed method study. Similarly, LaValley et al's study exploring consumer's experiences of their online search for health information found that different types of web sites shape users' online information‐seeking experiences and levels of frustration! It seems the continued efforts of librarians and healthcare professionals is needed to provide training to help consumers recognise and select web sites using established guidelines and quality criteria.…”
Section: In This Issue…mentioning
confidence: 99%